Hubungan Usia, Jenis Kelamin, dan Jarak Jahitan Luka dengan Kejadian Infeksi Luka Operasi pada Pasien Apendisitis Perforasi di RSUD Dr. H. Abdul Moeloek Provinsi Lampung Tahun 2020-2021 - Caesarridha, Dhaifany Karissa; Wintoko, Risal; Mustofa, Syazili; Soleha, Tri Umiana (CV. Jasa Sukses Abadi, 2024)
Surgical site infection is a type of nosocomial infection with the most common occurrence, which is 38% of all cases of nosocomial infection. The distance of sutures affects the local hemodynamics around the surgical wound and can cause the inhibition of thrombus formation which plays a role in the wound healing process so that it will inhibit wound healing which will lead to increase of bacterial growth and cause infection and tissue damage. This study is an unpaired comparative analytic method with a cross-sectional research design. The sampling technique is total sampling. The research subjects were patients with perforated appendicitis at RSUD Dr. H. Abdul Moeloek, Lampung in 2020-2021, totaling 37 people. The independent variable in this study were age, gender, and the distance between the sutures, while the dependent variable was the incidence of surgical site infection. The study showed that the distance of sutures had a correlation with the incidence of surgical site infection with a p value of 0.00 (<0.05), where the distance of sutures that <2 cm has a higher frequency of surgical site infections than the distance of sutures that ≥2 cm. Age also has a correlation with the incidence of surgical site infection with a p value of 0.041 (<0.05). Meanwhile, gender did not have a correlation with the incidence of surgical site infection with a p value of 0.728 (> 0.05). We can conclude that the distance of sutures and age have a correlation with the incidence of surgical site infection. Otherwise, gender is not associated with the incidence of surgical site infection.